ANALYSIS OF POSSIBLE COMPLICATIONS AFTER CHEMICAL TEETH WHITENING - Светлана Ивановна Токмакова; Людмила Юрьевна Побединская; Ольга Владимировна Бондаренко; Юлия Васильевна Луницына; Ольга Есеновна Бекжанова; Евгений Владимирович Мокренко (Медицина в Кузбассе)
Chemical teeth whitening is becoming an increasingly requested and popular procedure every year, and manufacturers are steadily expanding the range of whitening systems. Many doctors and patients do not have a full understanding and their own point of view about the existing risks of tooth color correction and the expediency of such procedures. Therefore, research in this direction remains relevant today.